Teoría y práctica de la historiografía hispánica medieval - Ward, Aengus (University of Birmingham Press, 2000)
DISPATCHED FROM USA. NO EXPEDITED SHIPPING! May contain remainder marks. Allow 14-21 business days for delivery. Before ordering please check the language in the product description. Over 6 million customers served. Order now. Selling online since 1995. Few left in stock - order soon. Code: P20100311114449S1902459083. SKU: 1902459083-1-PWLS.